Epstein Barr virus nuclear antigen 1 (EBNA-1) peptides recognized by adult multiple sclerosis patient sera induce neurologic symptoms in a murine model. Issue 106 (January 2020) - Jog, Neelakshi R.; McClain, Micah T.; Heinlen, Latisha D.; Gross, Timothy; Towner, Rheal; Guthridge, Joel M.; Axtell, Robert C.; Pardo, Gabriel; Harley, John B.; James, Judith A.
Abstract: Multiple sclerosis (MS) is an autoimmune demyelinating disease with progressive neurodegeneration and complex etiology likely involving genetic and environmental factors. MS has been associated with Epstein Barr virus (EBV) infection, with patients often showing enhanced responses to EBV antigens. To determine whether abnormal EBV nuclear antigen-1 (EBNA-1) humoral immunity can serve as an initiator of autoimmune responses in MS, we investigated the fine specificities of the humoral immune response against EBNA-1 in MS patients using solid phase epitope mapping. Antibodies from MS patients recognized an EBNA-1 epitope spanning amino acids 411–426, previously unknown to be recognized specifically by untreated MS patients. Antibodies against this epitope cross-reacted to myelin basic protein (MBP). Furthermore, animals immunized with this EBNA-1 polypeptide mounted a response against MBP and developed signs of experimental autoimmune encephalitis (EAE). These data support a link between MS and EBV through antibodies that cross-react between EBV proteins and the MBP autoantigen. Highlights: Adult MS patient antibodies recognize EBNA epitope spanning aa411-426 Anti-EBNA411-426 responses are diminished by interferon treatment Anti-EBNA411-426 cross-reacts with myelin basic protein (MBP) EBNA411-426 immunized mice mount immune responses toward MBP EBNA411-426 immunization causes clinical signs of neurologic disease in mice